CARICOM Regional Transformation Programme for Agriculture : the regional coconut industry : global market intelligence - Singh, R. H. ([UWI. Department of Agricultural Economics and Extension] [St. Augustine]TT, 2007)
Focuses on the coconut's major use as seed oil within the 'oils and fats' category. Examines and analyzes other minor and varied uses for coconut. Highlights some of the limiting factors from a regional context.